Malaria and Typhoid Fever Coinfection in the Hospital University of Bobo-Dioulasso, Burkina Faso - Ibrahim Sangaré; Yacouba Sourabié; Wilfried Wenceslas Bazié; Constant Sirima; Fabrice Da; Do Soufiane Sanou; Jacques Zoungrana; Armel Poda; Abdoul Salam Ouédraogo; Sanata Bamba (Journal of Parasite Research, 2019)
Malaria and typhoid fever are two endemic infectious diseases in developing tropical countries including Burkina Faso. There are two distinct infectious diseases with many similar clinical signs. In each sanitary area, it is important to describe the
Keywords: Malaria